Challenges Regarding the Use of Human Capital in the Contemporary Economy - Bătuşaru Cristina; Sbârcea Ioana (Studies in Business and Economics, 2020)
The paper addresses a topical and important issue for national economic activity, highlighting the important role that human capital has in ensuring economic development and growth. Given the increasingly dynamic and turbulent economic and social context, as a result of the expansion of the phenomena circumscribed by globalization, continuous training through education and the level of health of the population remain the main pillars in ensuring the competitiveness of human capital. Considering this reality, the paper presents a detailed analysis of Romania's position regarding the investment in education and health in a European context and the main elements that characterize the national human capital. By identifying the vulnerabilities associated with the qualitative and quantitative structure of the national human resource, a set of proposals and recommendations are formulated meant to constitute possible solutions for the reported problems. The main conclusions deriving from the study strengthen the hypothesis according to which the return of different forms of professional training is ensured by investing in education and health and represents the conditions of a competitive economic environment in which human capital is properly capitalized.